Endothelial IGF‐1 receptor mediates crosstalk with the gut wall to regulate microbiota in obesity. (2nd May 2021) - Haywood, Natalie J; Luk, Cheukyau; Bridge, Katherine I; Drozd, Michael; Makava, Natallia; Skromna, Anna; Maccannell, Amanda; Ozber, Claire H; Warmke, Nele; Wilkinson, Chloe G; Watt, Nicole T; Koch‐Paszkowski, Joanna; et al.
Abstract: Changes in composition of the intestinal microbiota are linked to the development of obesity and can lead to endothelial cell (EC) dysfunction. It is unknown whether EC can directly influence the microbiota. Insulin‐like growth factor‐1 (IGF‐1) and its receptor (IGF‐1R) are critical for coupling nutritional status and cellular growth; IGF‐1R is expressed in multiple cell types including EC. The role of ECIGF‐1R in the response to nutritional obesity is unexplored. To examine this, we use gene‐modified mice with EC‐specific overexpression of human IGF‐1R (hIGFREO) and their wild‐type littermates. After high‐fat feeding, hIGFREO weigh less, have reduced adiposity and have improved glucose tolerance. hIGFREO show an altered gene expression and altered microbial diversity in the gut, including a relative increase in the beneficial genus Akkermansia . The depletion of gut microbiota with broad‐spectrum antibiotics induces a loss of the favourable metabolic differences seen in hIGFREO mice. We show that IGF‐1R facilitates crosstalk between the EC and the gut wall; this crosstalk protects against diet‐induced obesity, as a result of an altered gut microbiota. SYNOPSIS: It remained unclear if gut endothelial cells can directly influence the microbiota. Here, endothelial specific over‐expression of IGF‐1R is shown to promote advantageous remodelling of the gut microbiota upon high fat diet, which protects against the development of obesity. Mice overexpressing insulin like growth factor‐1 receptors in the endothelium (hIGFREO) are protected against obesity. Protection against obesity is in part due to remodelling of the intestinal microbiota due to endothelium‐enterocyte crosstalk. Altered microbial diversity in the gut leads to a relative increase in the beneficial genus Akkermansia . Microbiota depletion using broad‐spectrum antibiotics attenuates advantageous metabolic phenotypes of hIGFREO mice. Abstract : It remained unclear if gut endothelial cells can directly influence the microbiota. Here, endothelial specific over‐expression of IGF‐1R is shown to promote advantageous remodelling of the gut microbiota upon high fat diet, which protects against the development of obesity.